2016
DOI: 10.1155/2016/1207393
|View full text |Cite
|
Sign up to set email alerts
|

P2Y Receptors in Synaptic Transmission and Plasticity: Therapeutic Potential in Cognitive Dysfunction

Abstract: ATP released from neurons and astrocytes during neuronal activity or under pathophysiological circumstances is able to influence information flow in neuronal circuits by activation of ionotropic P2X and metabotropic P2Y receptors and subsequent modulation of cellular excitability, synaptic strength, and plasticity. In the present paper we review cellular and network effects of P2Y receptors in the brain. We show that P2Y receptors inhibit the release of neurotransmitters, modulate voltage- and ligand-gated ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 164 publications
(179 reference statements)
1
60
0
1
Order By: Relevance
“…Thus, multiple ATP release sites exist in the normal brain [72]. ATP acts as a neurotransmitter and is released during synaptic transmission [73]. Astrocytes release ATP and thereby generate Ca 2+ waves as a propagating signal [74].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, multiple ATP release sites exist in the normal brain [72]. ATP acts as a neurotransmitter and is released during synaptic transmission [73]. Astrocytes release ATP and thereby generate Ca 2+ waves as a propagating signal [74].…”
Section: Discussionmentioning
confidence: 99%
“…Proconvulsive roles for P2Y 1 have been suggested by the observation that P2Y 1 receptor activation leads to enhanced Ca 2ϩ signaling and astroglial activation in experimental kindling, a model of epileptogenesis (Á lvarez-Ferradas et al, 2015). P2Y 1 has also been shown to regulate the release of different neurotransmitters in the brain, including glutamate, noradrenaline, and GABA, and to alter the sensitivity or availability of neurotransmitter receptors, including metabotropic glutamate receptor 1 (mGluR1), NMDA, gamma-aminobutyric acid (GABA A ), and P2X receptors (Guzman and Gerevich, 2016). A more recent study demonstrated that, although P2Y 1 antagonism had no effect on seizure severity, it significantly reduced seizureinduced neuronal loss in the hippocampus (Simoes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The P2Y2 and P2Y4 receptors activate phospholipase C, increasing the cytosolic Ca 2+ concentration from the intracellular reserves and the activation of protein kinase C in response to the production of inositol 1,4,5-trisphosphate and diacylglycerol, respectively [111]. Generally, P2Y receptors that increase intracellular Ca 2+ concentration induce the tricarboxylic acid cycle and increase ATP production, which promotes the maintenance of ion homeostasis and antioxidant defense [109].…”
Section: Molecular Perspectivesmentioning
confidence: 99%
“…P2Y2 receptors are expressed by neurons, astrocytes, and microglia and regulate actin polymerization and cytoskeletal rearrangements through the Rac/Rho pathways [112], as well as the P2Y4 receptors [113]. Its activation confers neuroprotection in several ways: the promotion of neurite outgrowth, increased cell motility, nonamyloidogenic processing of the amyloid precursor protein, and increased phagocytosis and degradation of the amyloid-beta peptide [102,111]. Moreover, studies have shown that microglia respond rapidly to nerve lesions by migrating to the spinal projection territories of the central terminals of injured primary afferents, with subsequent proliferation, activation of p38 MAPK and ERK1/2, and production of proinflammatory cytokines and chemokines [114].…”
Section: Molecular Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation